EFEKTIVITAS MODEL PJBL BERBANTUAN E-MODUL BERBASIS STEM DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF PADA MATERI ENERGI TERBARUKAN - Robi Aryanta Sembiring; Inov Ivoel Situmorang; Muhammad Ridho; Pio Situmorang; Mariati Purnama Simanjuntak (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effectiveness of the Project Based Learning (PjBL) model assisted by STEM-based e-modules in improving students' creative thinking skills on renewable energy material. The study used a quantitative descriptive method with a mini-research approach on 25 grade XI students and one physics teacher at SMA Negeri A. Data were collected through interviews and questionnaires using Google Forms, then analyzed descriptively quantitatively and qualitatively. The results showed that students' creative thinking skills were still low because learning was teacher-centered. The majority of students responded positively to the implementation of PjBL assisted by STEM-based e-modules because it was more interesting, interactive, and helped understand the material. Thus, the model has the potential to improve students' creative thinking skills in physics learning.